A new species of Sericanthe (Coffeeae, Rubiaceae) from Chimanimani Mountains, Mozambique-Zimbabwe border - Wursten, Bart; Bridson, Diane; Janssens, Steven B.; de Block, Petra (Phytotaxa, 2020)
The Chimanimani Mountains, located at the Mozambique-Zimbabwe border, are geologically unique in that they consist of quartzites giving rise to peaks and outcrops between zones of schist supporting grasslands. The nutrient-poor quartzitic soils house a high number of endemic plant species. One of these is Sericanthe chimanimaniensis, which is here described as new for science. We give a detailed description and distribution map, illustrations, information on ecology and phenology, and an assessment on the conservation status. An identification key to closely allied species is presented.